Experimental and modeling study of CO2 - Improved gas recovery in gas condensate reservoir - Zhengyuan Su; Yong Tang; Hongjiang Ruan; Yang Wang; Xiaoping Wei (Petroleum, 2017)
This paper presents the effectiveness of the CO2 injection process at different periods during gas-condensate reservoir development. Taking a real gas-condensate reservoir located in China's east region as an example, first, we conducted experiments of constant composition expansion (CCE), constant volume depletion (CVD), saturation pressure determination, and single flash. Next, a series of water/CO2 flooding experiments were been investigated, including water flooding at present pressure 15 MPa, CO2 flooding at 25.53 MPa, 15 MPa, which repents initial pressure and present pressure respectively. Finally, the core flooding numerical model was constructed using a generalized equation-of-state model reservoir simulator (GEM) to reveal miscible flooding mechanism and the seepage flow characteristics in the condensate gas reservoir with CO2 injection. A desirable agreement achieved in experimental results and predicted pressure volume temperature (PVT) properties by the modified equation of state (EOS) in the CVD and CCE tests indicated that the proposed recombination method can successfully produce a fluid with the same phase behavior of initial reservoir fluid with an acceptable accuracy. The modeling results confirm the experimental results, and both methods indicate that significant productivity loss can occur in retrograde gas condensate reservoirs when the flowing bottom-hole pressure falls below dew point pressure. Moreover, the results show that CO2 treatment can improve gas productivity by a factor of about 1.39 compared with the water flooding mode. These results may help reservoir engineers and specialists to restore the lost productivity of gas condensate.